Wyznaczanie położenia konturów złożowych dla złóż ropy naftowej w oparciu o kryteria hydrodynamiczne, z uwzględnieniem zmiennej gęstości płynów złożowych i ciśnień kapilarnych - Zawisza, Ludwik (My University, 2007)
The size and magnitude of a reservoir trap are determined by the geologic boundaries of strata and contour of the reservoir. The location of contours is determined by the movement of the fl owing reservoir water, reservoir properties of rocks and properties of reservoir fluids. An original methodics of mapping reservoir traps for oil is presented in the paper. The method employs both the influence of groundwater dynamics and also variability of density of reservoir fluids and the capillary pressure effect on the location of the contours. It enables determining locations of hydrodynamic traps in a 3D space, in the condition of fl owing water and high variability of properties of reservoir rocks and reservoir fluids. The method also enables determining reservoir contours both in the structural and stratigraphic type of reservoir. The realization of the presented method of mapping reservoir traps in presented on the example of oil fields Pomorsko and Czerwieńsk, occurring in the Main Dolomite beds in the Fore-Sudetes area.

Wielkość i kształt pułapki złożowej wyznaczają granice geologiczne warstw oraz powierzchnia konturu złożowego. Na położenie konturów złożowych mają wpływ ruch przepływających wód złożowych, własności zbiornikowe skał oraz własności płynów złożowych. W pracy przedstawiono oryginalną metodykę kartowania pułapek złożowych dla ropy naftowej. Metodyka ta uwzględnia wpływ zarówno dynamiki wód podziemnych, jak i zmian gęstości płynów złożowych oraz efektu ciśnienia kapilarnego na położenie konturów złożowych. Pozwala ona na wyznaczenie położenia hydrodynamicznych pułapek złożowych w przestrzeni trójwymiarowej, w warunkach przepływających wód oraz dużej zmienności własności skał zbiornikowych i płynów złożowych. Metodyka ta umożliwia wyznaczanie konturów złożowych zarówno w złożach typu masywowego, jak i w złożach typu warstwowego. Realizację opracowanej przez autora metodyki kartowania pułapek złożowych przedstawiono na przykładzie złóż ropy naftowej Pomorsko i Czerwieńsk, występujących w utworach dolomitu głównego, na obszarze przedsudeckim.
Determining location of reservoir contours for oil deposits on the basis of hydrodynamic criteria, and accounting for the changing density of reservoir fluids and capillary pressures
Wiertnictwo, Nafta, Gaz
Keywords: hydrodynamics; capillary pressure; hydrodynamika; petroleum traps; ciśnienie kapilarne; pułapki węglowodorów; oil-water contour; kontury złożowe